PEMANFAATAN GOOGLE ANALYTICS UNTUK MENINGKATKAN SEARCH ENGINE OPTIMIZATION WEBSITE - Muhammat Rasid Ridho (Universitas Putera Batam, 2015)
To bring in a lot of website visitors is fairly difficult challenges to face, either because more and more websites are popping up with the same theme with us and because of the difficulty of making the content or content that is burdensome. Google Analytics can be utilized to analyze the content which are much in demand, then we can take a decision on what to do next. Most companies have a great site, but only about five percent of the knowing use of Search Engine Optimization (SEO) as part of the marketing plan. If they use their SEO will usually learn and spend thousands of dollars to make the site the number one but still too many visitors. We hope that if someone is typing a particular key word in the search engine google.com for example, the website we at least be in the top ten on the first page or even if it could be at the top.